Multiply all terms in the first equation by 2 and all terms in the second by 3.
You should obtain:
6x + 16y = 34
-6x + 27y = 9
------------------
43y =43, and so y = 1. Subbing 1 for y in the first eq'n, we get
3x + 8(1) = 17, or 3x = 9, or x = 3.
The solution is (3, 1).
Answer:
16
Step-by-step explanation:
Answer:
The solution is (2, -2)
Step-by-step explanation:
In order to solve this, multiply the second equation by -5 and then add through.
5x - 4y = 18
-5x - 15y = 20
------------------
-19y = 38
y = -2
Now that we have the value of y, we can solve for x.
x + 3y = -4
x + 3(-2) = -4
x - 6 = -4
x = 2
Venus is the awnser to that question